Advances in exercise to alleviate sarcopenia in older adults by improving mitochondrial dysfunction - Zhu, Yang; Zhou, Xuchang; Zhu, Aiyuan; Xiong, Shijing; Xie, Jun; Bai, Zhenmin (Frontiers in Physiology, 2023)
Sarcopenia is a chronic degenerative disease affecting primarily older adults. A growing aging population is gradually increasing the number of patients suffering from sarcopenia, placing increasing financial pressure on patients' families and society in general. There is a strong link between mitochondrial dysfunction and sarcopenia pathogenesis. As a result, treating sarcopenia by improving mitochondrial dysfunction is an effective strategy. Numerous studies have demonstrated that exercise has a positive effect on mitochondrial dysfunction when treating sarcopenia. Exercise promotes mitochondrial biogenesis and mitochondrial fusion/division to add new mitochondria or improve dysfunctional mitochondria while maintaining mitochondrial calcium homeostasis, mitochondrial antioxidant defense system, and mitochondrial autophagy to promote normal mitochondrial function. Furthermore, exercise can reduce mitochondrial damage caused by aging by inhibiting mitochondrial oxidative stress, mitochondrial DNA damage, and mitochondrial apoptosis. Exercise effectiveness depends on several factors, including exercise duration, exercise intensity, and exercise form. Therefore, Moderate-intensity exercise over 4 weeks potentially mitigates sarcopenia in older adults by ameliorating mitochondrial dysfunction. HIIT has demonstrated potential as a viable approach to addressing sarcopenia in aged rats. However, further investigation is required to validate its efficacy in treating sarcopenia in older adults.